The Role of Functional Performance in Managing Sports Championships and Competitions from the Perspective of Managers(A field study of M’sila wilaya leagues ) - Hebache Kamel (Université de M'sila, 2022)
Abstract: This study aims at highlighting the role of functional performance in managing sports championships and competitions from the perspective of wilaya of M’sila leagues managers This study Is carried out using the analytic descriptive method and the sample of study consists of thirty membres from the managing offices of wilaya leagues through a simple random sampling method. Also, data collection was based on functional performance measurement. This latter consists of three dimensions: the effort exerted, individual capabilities and the individual’s awareness of his functional duty dimension .Each dimension is composed of seven questions. Moreover, study concludes that there is a positive role for the functional performance in managing sports championships and competitions from managers’ perspective. And one of the most important recommendations of this study: provide good league centers because we have noticed that most leagues do not have good and suitable centers for doing activities.
Keywords: Keywords: Functional performance, sports championships and competitions, sports manager, sports League